Enigmatic Cervicofacial Actinomycosis Post Radiotherapy - A Case Report - Phoon Nguyen, Amanda (UI Scholars Hub, 2023)
Although thought to be uncommon, it is believed that cervicofacial actinomycosis is underreported due to frequent misdiagnosis. It has been called the “most misdiagnosed disease by experienced clinicians”. A wide range of dental procedures or trauma, including tooth eruption, may precipitate actinomycosis by enabling microorganisms to penetrate the deeper tissue layers via an entry point. This infective disease is significant due to its potentially aggressive and locally destructive nature. This case describes a patient diagnosed with cervicofacial actinomycosis. Her history prior to this was significant for proliferative verrucous leukoplakia, and T4aN0M0 (AJCC 7th Edition) squamous cell carcinoma of the right hard palate for which she received surgery and post-operative radiotherapy. The mechanism of actinomycotic infection, its presentation, differential diagnosis, and management is discussed, with review of the relevant literature. This case highlights an unusual case of cervicofacial actinomycosis and demonstrates the complexities in reaching a definitive diagnosis in cases of osteomyelitis and osteoradionecrosis with significant bacterial burden.